Anticancer immunotherapy by CTLA-4 blockade: obligatory contribution of IL-2 receptors and negative prognostic impact of soluble CD25: corrigendum - Hannani, Dalil; Vétizou, Marie; Enot, David; Rusakiewicz, Sylvie; Chaput, Nathalie; Klatzmann, David; Desbois, Melanie; Jacquelot, Nicolas; Vimond, Nadège; Chouaib, Salem; Mateus, Christine; Allison, James P.; et al. (Cell research, 2015)
Correction to: Cell Research (2015) 25:208-224. doi:10.1038/cr.2015.3; published online 13 January 2015 The authors apologize for omission of two authors, Inka Zörnig (Department of Medical Oncology, National Center for Tumor Diseases and Heidelberg University Hospital, Heidelberg, Germany) and Jessica Hassel (Department of Dermatology, National Center for Tumor Diseases and Heidelberg University Hospital, Heidelberg, Germany), in the author list.
Gesehen am 08.06.2021
The original article was published online 13 January 2015